INFLUENCE OF TEMPERAMENT TYPES ON THE ACTIVITIES OF EMPLOYEES OF THE ENTERPRISE - Abitkhan Sabitkhanovich Shakirov (European Science Publishing, 2024)
To achieve the greatest efficiency and results of employees' work, it is important to know and take into account the characteristics of the activities, communication and relationships in accordance with the temperament of each specialist. Based on these observations and knowledge of temperament, create comfortable conditions in the workplace, a psychological climate for the fruitful activity of personnel, find suitable ways to influence subordinates, while strictly observing the personal type of temperament. Also skillful communication with clients, partners, Be able to choose the forms of communication necessary to build mutually beneficial and advantageous relationships and avoid conflicts. The relevance of this article is the study of temperament in conjunction with the activities of personnel and their psychological qualities.
Keywords: Temperament, melancholic, phlegmatic, choleric, sanguine, team, personnel, personality, type.